(untitled) (Indian Journal of Animal Production and Management, 2013)
Dicalcium phosphate (DCP) is used traditionally as phosphorus supplement in poultry diets. However, due to high demand and scarce availability, its cost is steeply increasing. Therefore, to reduce the cost of mineral mixture, it has become imperative to use alternate and economical phosphorus supplement in poultry diet without lowering the production performance of birds and reducing the cost of their production. One of the alternates is rock phosphate (RP) which is available in plenty at much lower cost compared to DCP. The performance of birds on RP varies greatly probably because of large variations in the fluorine (F) content (205 to 5540 mg/kg) of the diets based on RP. Therefore, this study has been planned to see the utilization of rock phosphate instead of dicalcium phosphate on the growth performance of egg type growing chicken. In the experiment, three hundred and twenty four WLH growing pullets (08 weeks age) were randomly distributed to 27 replicates of 12 pullets each and were allotted to 9 dietary treatments. Diet one (T1) was control. Diets 2, 4, 6 and 8 (T 2, T4, T6 and T8) were same as T1 except that in these diets DCP was replaced @ 40%, 60%, 80% and 100% with rock phosphate. While, diets 3, 5, 7 and 9 (T 3, T5, and T7and T9) were same as T 2, T4, T6 and T8 accept the addition of aluminium at a ratio of 0.8 Al: 1 F, in those diets. Experiment was conducted for 9-20 weeks (Grower phase). The overall performance of growers offered RP diets indicated that increase in the level of RP reduced their performance (weight gain, feed intake, FER and PI), significantly. However, it was significant when level of RP was increased above 40%. 60% replacement of DCP with RP supplemented with aluminium sulphate did not influence the weight gain, feed intake FER and PI and led to better performance in growers. The cost per kg weight gain has certainly increased due to use of higher levels of RP supplemented with aluminium sulphate.Hence it was concluded that 40% RP and 60% RP along with aluminium sulphate was beneficial to replace DCP in the mineral mixture of egg type growers. However, supplementation of aluminium sulphate to RP was not economical.